2022
DOI: 10.1186/s12902-022-01084-6
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in circulating levels of vitamin D binding protein, total and bioavailability of vitamin D in diabetic retinopathy patients

Abstract: Aims This study aimed to investigate the association between circulating levels of vitamin D binding protein (VDBP) and its genotypes and diabetic retinopathy risk. Methods This case–control study recruited 154 patients with type 2 diabetes mellitus; 62 with diabetic retinopathy (DR) and 92 without DR and diabetic nephropathy (DN). Circulating levels of 25-hydroxyvitamin D3 and VDBP levels were measured in the patients. The genotype and phenotype o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Vitamin D-binding protein (VDBP) levels are reduced in diabetic individuals with retinopathy, potentially due to VDBP being excreted in the urine because of tubular dysfunction in diabetic patients. Alternatively, decreased VDBP levels could contribute to the advancement of DR by obstructing the microvessels in the retina [ 57 ]. Regular vit.…”
Section: Diabetic Retinopathy (Dr) and Diabetic Macular Edema (Dme)mentioning
confidence: 99%
“…Vitamin D-binding protein (VDBP) levels are reduced in diabetic individuals with retinopathy, potentially due to VDBP being excreted in the urine because of tubular dysfunction in diabetic patients. Alternatively, decreased VDBP levels could contribute to the advancement of DR by obstructing the microvessels in the retina [ 57 ]. Regular vit.…”
Section: Diabetic Retinopathy (Dr) and Diabetic Macular Edema (Dme)mentioning
confidence: 99%
“…It has also been suggested that the balance of inflammatory mediators is disrupted in diabetic retinopathy, which results in the production of vascular endothelial growth factors, chemokines, and adhesion molecules that lead to retinal vascular damage 5 , 6 . Moreover, some studies have suggested that vitamin D deficiency is closely associated with diabetic retinopathy 7 , 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%